Analisis Variabel Ketenagakerjaan Terhadap Produktivitas Pekerja Indonesia Tahun 2022 - Widiyasari, Amalia Isti; A'mal, Ikhlasul; Putri Yunardi, Nabila Fatma; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2023)
The lack of a workforce-to-employment-opportunity balance on the Indonesian labor market in 2022 is worrisome. In an effort to make the workforce more competitive, labor productivity indicators are available on the labor market itself. This study aims to analyze the level of labor productivity in Indonesia in terms of quality in the economic development pillars in achieving the eighth Sustainable Development Goals (SDGs). This study uses K-Means Clustering and multiple linear regression analysis. Based on the K-Means Clustering method, three provincial clusters were obtained with levels of labor productivity from lowest to highest. The results showed that the open unemployment rate and the percentage of the labor force with basic education significantly reduced labor productivity, while the wage rate significantly increased labor productivity. Improving the labor market by looking at labor productivity and the variables that influence it in Indonesia can be carried out in an efficient manner according to the areas that have been mapped by implementing employment innovations.